2016
DOI: 10.1093/fampra/cmw057
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with intellectual disabilities and carers in GP health information exchanges: a qualitative study

Abstract: There is considerable HIE potential in patients themselves, as well as in their network, although many barriers have to be overcome to profit from this. GP practices are recommended to adjust consultations and communication practices and to facilitate deployment of the patient's network, while still considering patient autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
(42 reference statements)
4
22
0
1
Order By: Relevance
“…Participants with DS, parents and support staff reported that PDS generally needed support deciding about visiting a doctor, making appointments with healthcare professionals, communicating during consultations, and sharing health or treatment information with (other) healthcare professionals, support staff, parents or other relatives. This is in line with literature on adults with intellectual disability in primary care (Mastebroek et al, ). When PDS were living with their parents, parents offered this support.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Participants with DS, parents and support staff reported that PDS generally needed support deciding about visiting a doctor, making appointments with healthcare professionals, communicating during consultations, and sharing health or treatment information with (other) healthcare professionals, support staff, parents or other relatives. This is in line with literature on adults with intellectual disability in primary care (Mastebroek et al, ). When PDS were living with their parents, parents offered this support.…”
Section: Resultssupporting
confidence: 91%
“…Parents expressed worries such as “Does support staff notice symptoms of my son/daughter in time?” and “What will happen with my son/daughter when I die?” especially when their child would soon be leaving home or when parents were old. Parents and support staff agreed that support staff did not have a high level of (DS‐specific) medical knowledge, which is consistent with the literature (Mastebroek et al, ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“… 9 These uncertainties may be adding to difficulties in the exchange of health information between carers and GPs and GP practices not being fit to the consultation and communication needs of people with ID. 29 30 Good practice depends on the knowledge, and flexibility of individual carers and healthcare professionals, which has been shown to lead to reasonable adjustments being initiated random throughout organisations. 31 More insight into the nature of out-of-hours primary care requests will help to appoint reasonable adjustments that are structural to address avoidable care, make out-of-hours primary care better accessible and effectively manage needs of people with ID at GP cooperatives.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also underpinned by Mastebroek et al Moreover, their findings highlighted the importance of a personal connection with care professionals. 43 In order to enable PDs to engage in their care, primary-care professionals should invest in their therapeutic relationship with patients (with a disability). 9 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%